Preparing future-ready graduates through halal entrepreneurship education: reflections from four years of teaching and income-generation training - Elgharbawy, Amal A.M.; Wan Sulaiman, Wan Syibrah Hanisah; Yuhan, Avicenna (IIUM Press, 2026)
The rapid expansion of the global halal economy presents new opportunities for graduates to create value through ethical, innovation-driven enterprises. This paper reflects on four years of teaching the Halal Entrepreneurship course at the International Islamic University Malaysia (IIUM), where the pedagogical approach intentionally goes beyond theoretical instruction to train students in halal-compliant income generation, digital business models, and ethical entrepreneurial behaviour grounded in Maqasid al-Shari’ah principles. The study adopts an autoethnographic approach, using the instructors' self-reflection, supported by teaching notes, course artefacts, and informal feedback collected over four consecutive years. The course design integrates value-centric teaching, digital marketplace training, and project-based entrepreneurship, enabling students to apply halal concepts to practical business activities that generate real revenue. Cross multiple student cohorts delivered over four academic years, during which the course was offered twice per year, students demonstrated the capacity to conceptualise halal business models, conduct fundamental market analysis, price products responsibly, and utilise digital platforms for sales and branding. Observations indicate that early exposure to Halal Entrepreneurship reduces fear of business failure, strengthens ethical decision-making, and improves student confidence in economic participation through self-employment and small-scale start-ups. The paper illustrates how a values-based entrepreneurship curriculum supports the development of future-ready talent for the digital economy, encourages inclusive economic governance, and contributes to the broader halal innovation landscape